The Diagnosis Is in the Smear: A Case and Review of Spur Cell Anemia in Cirrhosis - Raffa, Gabriella A. (Case Rep Hematol, 2021)
The etiology of anemia in liver cirrhosis is multifactorial; one less recognized cause is hemolytic anemia due to spur cells, known as spur cell anemia. We present the case of a 57-year-old woman with alcoholic cirrhosis who presented with symptomatic macrocytic anemia with a hemoglobin level of 7.4 g/dL and signs of decompensated liver disease. Notably, she had no signs of overt bleeding. Further workup was consistent with hemolysis, with peripheral smear demonstrating spur cells. The patient was treated with both steroids and IVIG, although she eventually expired. The characteristic morphology of spur cells is due to alteration of the lipid composition of the erythrocyte membrane, changing its shape and leading to splenic sequestration and destruction. Characteristic of this disorder is an increased ratio of cholesterol to phospholipid on the membrane, as well as low levels of apolipoproteins and low- and high-density lipoproteins. The presence of spur cells is an indicator of poor prognosis and high risk of mortality. Currently, the only definitive cure is liver transplantation. There is a paucity of literature on the prevalence of this phenomenon and even less about treatment. This case highlights the importance of recognition of spur cell anemia as a cause of anemia in cirrhosis as well as the importance of the peripheral smear in the diagnostic workup. Early recognition can lead to avoidance of unnecessary procedures. Further research is needed to elucidate the true prevalence of spur cell anemia and examine further treatment options.